2007
DOI: 10.1074/jbc.m701665200
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomic Identification and Biological Validation of Neuroendocrine Regulatory Peptide-1 and -2

Abstract: Recent advances in peptidomics have enabled the identification of previously uncharacterized peptides. However, sequence information alone does not allow us to identify candidates for bioactive peptides. To increase an opportunity to discover bioactive peptides, we have focused on C-terminal amidation, a post-translational modification shared by many bioactive peptides. We analyzed peptides secreted from human medullary thyroid carcinoma TT cells that produce amidated peptides, and we identified two novel amid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 34 publications
4
124
0
Order By: Relevance
“…Upon processing by the neuroendocrine-specific prohormone convertases PC1/3 and PC2, VGF may yield a number of peptides that are stored in dense core granules and secreted through regulated pathways [66]. Up to now, six VGFpeptides were shown to modulate with a remarkable peptide-specific selectivity, a diverse range of biological functions such as synaptic plasticity, apoptosis, sexual antidepressant-like behavior and inflammatory pain [2,7,10,11,35,37,58,63,64,65,70].…”
Section: Introductionmentioning
confidence: 99%
“…Upon processing by the neuroendocrine-specific prohormone convertases PC1/3 and PC2, VGF may yield a number of peptides that are stored in dense core granules and secreted through regulated pathways [66]. Up to now, six VGFpeptides were shown to modulate with a remarkable peptide-specific selectivity, a diverse range of biological functions such as synaptic plasticity, apoptosis, sexual antidepressant-like behavior and inflammatory pain [2,7,10,11,35,37,58,63,64,65,70].…”
Section: Introductionmentioning
confidence: 99%
“…In cells and tissues, proteolytic processing yields diverse peptides, including some of low MW, which were preferentially released by various stimuli (Possenti et al 1989, Trani et al 1995. These include peptides encompassing the VGF C-terminal portion, TLQP-21 and TLQP-62 peptides, and the recently identified peptides NERP-1 and -2 (Trani et al 2002, Bartolomucci et al 2007, Yamaguchi et al 2007, Bozdagi et al 2008. While vgf gene expression is distinctly modulated in multiple models and conditions (Levi et al 2004), differential processing and modulation of VGF peptides have been shown so far in the pituitary (Brancia et al 2005), adrenal glands (D'Amato et al 2008) and pancreas (Cocco et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The vgf gene (non-acronymic) and its peptide products are proposed neuroendocrine regulators affecting food intake and/or energy balance (Salton et al 2000, Levi et al 2004, as well as other functions including water balance (Yamaguchi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Vgf is a component of the chromogranin/secretogranin family 47, 48 actively involved in amyotrophic lateral sclerosis (ALS) neuroprotection 49. Because it is described that declined levels of this bioactive peptide (Vgf) could promote neurodegeneration 50, further investigation of these aspects is required.…”
Section: Discussionmentioning
confidence: 99%